Alteration of cGAS-STING signaling pathway components in the mouse cortex and hippocampus during healthy brain aging - Passarella, Sergio; Kethiswaran, Shananthan; Brandes, Karina; Tsai, I-Chin; Cebulski, Kristin; Kröger, Andrea; Dieterich, Daniela C.; Landgraf, Peter (Frontiers in Aging Neuroscience, 2024)
The cGAS-STING pathway is a pivotal element of the innate immune system, recognizing cytosolic DNA to initiate the production of type I interferons and pro-inflammatory cytokines.This study investigates the alterations of the cGAS-STING signaling components in the cortex and hippocampus of mice aged 24 and 108 weeks. In the cortex of old mice, an increase in the dsDNA sensor protein cGAS and its product 2'3'-cGAMP was observed, without corresponding activation of downstream signaling, suggesting an uncoupling of cGAS activity from STING activation. This phenomenon may be attributed to increased dsDNA concentrations in the EC neurons, potentially arising from nuclear DNA damage. Contrastingly, the hippocampus did not exhibit increased cGAS activity with aging, but there was a notable elevation in STING levels, particularly in microglia, neurons and astrocytes. This increase in STING did not correlate with enhanced IRF3 activation, indicating that brain inflammation induce by the cGAS-STING pathway may manifest extremely late in the aging process. Furthermore, we highlight the role of autophagy and its interplay with the cGAS-STING pathway, with evidence of autophagy dysfunction in aged hippocampal neurons leading to STING accumulation. These findings underscore the complexity of the cGAS-STING pathway's involvement in brain aging, with regional variations in activity and potential implications for neurodegenerative diseases.